Online group psychodynamic psychotherapy—The effectiveness and role of attachment—The results of a short study - Wajda, Zbigniew; Kapinos-Gorczyca, Agnieszka; Lizińczyk, Sebastian; Sitnik-Warchulska, Katarzyna; Izydorczyk, Bernadetta (Frontiers in Psychiatry, 2022)
The role played by remote treatment, including psychotherapy, has increased during the period of the Covid-19 pandemic. The results of research in this area are promising, initially pointing to a similar effectiveness for online psychotherapy as that of face-to-face psychotherapy. A significantly smaller amount of research has been conducted on online group psychotherapy, in particular in psychodynamic paradigm, while many authors have drawn attention to the need to conduct further research, with consider specific patients features. Conducted short study: pre- and post-treatment (10-weeks) and a 6-week follow-up on the effectiveness of online synchronous group psychodynamic psychotherapy (via Zoom) taking into consideration patient adulthood attachment. Twenty two patients with a diagnosis of neurotic or depressive took part in study. The instruments were used: the Symptom Checklist – 27PL, the Rosenberg Self-Esteem Scale, the De Jong Gierveld Loneliness Scale and Experience in Close Relationships. The results showed a lessening in the global severity of psychiatric symptoms (d=-0.526) and depressive symptoms (d=-0.5) as well as an increase in self-esteem (d=0.444) and feelings of loneliness (d=0.46). Observed also was a change in the attachment dimension: anxiety (d=-0.557) and avoidance (d=-0.526). The above results were maintained in the test conducted on the 6-week follow-up, as well as there being noted a reduction in social phobia symptoms. Attachment dimensions in general were not a predictor of the effectiveness of psychotherapy, with only a lessening in avoidance during the course of therapy constituted a predictor of increased symptoms of pain. The results of the research are promising with regard to psychiatric symptoms and increased self-esteem. During the course of therapy there may occur a favorable change in the attachment dimensions but this variable has not turned out to be a results predictor. Equally unconfirmed was the hypothesis known in the subject literature that online psychotherapy may be especially useful for individuals high on avoidance. As undesirable maybe interpreted the increase in the sense of patient loneliness as well as of symptoms of pain with a decrease in the avoidance dimension. These results will require further more controlled research.